External control of the public water supply in 29 Brazilian cities - Suzely Adas Saliba Moimaz; Orlando Saliba; Fernando Yamamoto Chiba; Nemre Adas Saliba (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The fluoridation of public water supplies is considered the most efficient public health measure for dental caries prevention. However, fluoride levels in the public water supply must be kept constant and adequate for the population to gain preventive benefit. The aim of this study was to analyze fluoride levels in the public water supply of 29 Brazilian municipalities during a 48-month period from November 2004 to October 2008. Three collection sites were defined for each source of municipal public water supply. Water samples were collected monthly and analyzed at the Research Laboratory of the Nucleus for Public Health (NEPESCO), Public Health Postgraduate Program, Araçatuba Dental School (UNESP). Of the 6862 samples analyzed, the fluoride levels of 53.5% (n = 3671) were within the recommended parameters, those of 30.4% (n = 2084) were below these parameters, and those of 16.1% (n = 1107) were above recommended values. Samples from the same collection site showed temporal variability in fluoride levels. Variation was also observed among samples from collection sites with different sources within the same municipality. Although 53.5% of the samples contained the recommended fluoride levels, these findings reinforce the importance of monitoring to minimize the risk of dental fluorosis and to achieve the maximum benefit in the prevention of dental caries.